Simulation of the flow inside an annular can combustor - Kadhim, Wael; Alkhafagiy, Dhirgham; Shires, Andrew (International Journal of Engineering and Technology, 2014)
In the gas turbine combustion system, the external flows in annuli play one of the key roles in controlling pressure loss, air flow distribution around the combustor liner, and the attendant effects on performance, durability, and stability. This paper describes a computational fluid dynamics (CFD) simulation of the flow in the outer annulus of a can combustor. Validating this simulation was done with experimental results obtained from analyzing the flow inside a can combustor annulus that was used in a Babylon/Iraq gas turbine power station. Pitot static tubes were used to measure the velocity in ten stations in the annular region. By using the velocity profile for comparison, a good agreement between the CFD simulation and experimental work was observed. Nomenclature: R: radius of combustor (mm) r: local radius (mm) Pt: total pressure (Pascal) Ps: static pressure (Pascal) DG: damp gap (mm) X/Dc: axial distance is normalized with the diameter of the casing as the origin. A, B and L: station of measurement and investigated locations. u: local axial velocity U: mass average axial velocity at inlet Keywords: Annulus Flow, Can Combustor, CFD Simulation, Pitot Static Tube, Velocity Profile.